Equivalent Circuit Modeling and Analysis of Low-Frequency Electromagnetic Metasurface-Based Wireless Power Transfer Systems - Wang, Kaiyuan; Yang, Junxiang; Lai, Ching-Ming; Yang, Yun (IEEE Conference on Industrial Electronics and Applications (Online), 2025)
Low-frequency electromagnetic metasurfaces (LEMTSs) have demonstrated significant potential in enhancing magnetic coupling and extending the power transfer distance in wireless power transfer (WPT) systems. However, the intricate circuit topology of LEMTS-based WPT systems presents challenges in isolating and analyzing the specific impact of the LEMTS. To address this, the paper proposes an equivalent circuit model for LEMTS-integrated WPT systems. Notably, the model adopts a simplified approach by neglecting cross-coupling effects among LEMTS elements. In this framework, the influence of the LEMTS is represented as an additional impedance and mutual inductance within a conventional two-coil WPT configuration. Both simulation and experimental results validate the accuracy and effectiveness of the proposed model.